Increasing Lecturers’ Work Motivation Through the Strengthening of Tolerance, Religiosity, and Gotong Royong - Hardhienata, Soewarto; Setyaningsih, Sri; Sutisna, Didi; Triningsih, Triningsih (PPSDP International Journal of Education, 2025)
This research highlights the importance of lecturers’ work motivation in achieving the goals of higher education institutions. Lecturers with high work motivation tend to contribute more significantly to the success of the institution. This study identifies gotong royong, religiosity, and tolerance as the main determinants influencing lecturers’ work motivation. Through Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis, it was found that gotong royong and tolerance significantly affect lecturers’ work motivation, both directly and indirectly through tolerance as a mediator. However, religiosity did not show a significant impact on lecturers’ work motivation. The results of the Importance Performance Map Analysis (IPMA) indicate that gotong royong has the highest importance value in influencing lecturers’ work motivation, followed by tolerance, while tolerance showed the best performance in practice. The practical implications of these findings are that higher education management should pay more attention to strengthening the practices of gotong royong and tolerance to improve lecturers’ work motivation. Developing programs based on gotong royong and tolerance is expected to effectively enhance lecturers’ work motivation. This study also has limitations, such as the restricted generalizability of the results to institutions outside the Jakarta area and the possibility of other unidentified factors. Therefore, further research is necessary to expand the understanding of other variables affecting lecturers’ work motivation and to consider additional relevant variables.